Solitary fibrous tumour of the tongue of an adolescent – a case report with immunohistochemical studies - Jabłońska, Joanna; Jesionek-Kupnicka, Dorota; Kordek, Radzisław (Polish Journal of Pathology, 2009)
Solitary fibrous tumour (SFT) is a rare, spindle-cell, mesenchymal neoplasm with haemangiopericytoma-like branching vascular pattern. The tumour has been reported in various locations but the oral cavity is a distinctly uncommon region. We describe a case of solitary fibrous tumour (SFT) in the tongue of a 15-year-old girl. Microscopically it had features characteristic for SFT and a common immunohistochemical profile but uncommonly increased mitotic count